A Middle-Aged Man Presenting With Progressive Heart Failure, Myopathy, and Monoclonal Gammopathy of Uncertain Significance - Broch, Kaspar (JACC Case Rep, 2020)
A 48-year-old man presented with rapidly progressive heart failure and monoclonal gammopathy of uncertain significance. No specific cause was detected on endomyocardial biopsy. As the heart failure worsened, he also developed progressive skeletal myopathy. This provided the clue to the diagnosis, and cardiac function recovered rapidly with cause-directed therapy. (Level of Difficulty: Intermediate.)